The Use of Code Mixing in English Literacy UTBK 2023 Teaching Videos in Ruang Guru Youtube Channel - Nurhasanah; Nurholis; Wardoyo, Cipto (Edukasi Lingua Sastra, 2025)
This research investigates the use of code mixing in English language teaching in the YouTube channel. The main purpose of this research is to find out the use of code mixing applied by teachers in English literacy teaching videos on the Ruang Guru YouTube channel. This research method is a qualitative method with a descriptive approach. Data collected through video transcription from Ruang Guru YouTube channel and analyzed based on Musyken's (2000) classification which includes Insertion, Alternation, and Congruent Lexicalization. The results showed that Insertion is the most dominant type of code mixing with a percentage of (51.67%), followed by Alternation (45.00%) and Congruent Lexicalization (3.33%). In addition, the use of code mixing by teachers as a teaching strategy is divided into two main strategies, namely: English word repetition and translation of words or sentences into Indonesian. The contribution of this research is to provide new insights into how code mixing can be used as an effective teaching strategy in a digital context and optimize the use of code mixing so that content becomes more accessible and comprehensible to diverse audiences.